Dermatologic Surgery and Procedures - Vereecken, Pierre (IntechOpen, 2018)
This book is intended for dermatologists, skin surgeons, and general practitioners who are interested in skin surgery and cosmetic procedures. The topics of broad and current interest in shaping the practice nowadays have been selected by the editor, Dr. Pierre Vereecken, MD, PhD, allowing the reader to expand his/her skills and surgical techniques. This book aims to meet the need for a practical guide to help the clinicians to extend their offer in daily practice in dermatology and corrective and skin cancer surgery.